Sympathetic efferent neurons are less sensitive than nociceptors to 4 Hz sinusoidal stimulation - Jonas, Robin; Namer, Barbara; Schnakenberg, Mark; Soares, Sabrina; Pakalniškis, Julius; Carr, Richard; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2020)
Background - Sinusoidal current stimuli preferentially activate C‐nociceptors. Sodium channel isoforms NaV1.7 and NaV1.8 have been implicated in this. Sympathetic efferent neurons lack NaV1.8 and were explored upon sinusoidal activation.
First published: 08 August 2019
Gesehen am 19.01.2021